2019
DOI: 10.1099/jmm.0.001003
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the effect of smoking on the buccal microbiome using next-generation sequencing technology

Abstract: Component Cap color Storage conditions 2X Environmental Master Mix Orange Shipped at-20°C. After first use, store at 2-8°C if used frequently, otherwise store at-20°C. Protect the 2X Environmental Master Mix from light. DNA Dilution Buffer Clear 16S Primer Set V2-4-8 (10X) Green Store at-15 to-25°C. 16S Primer Set V3-6, 7-9 (10X) Blue Negative Control White E. coli DNA control (30 µg/mL) Red Store at-15 to-25°C. Store separately from other reagents to prevent cross-contamination. Note: For safety and biohazard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 35 publications
4
26
2
Order By: Relevance
“…Megasphaera micronuciformis were reported to be found more commonly in cigarette smoker's upper gastrointestinal tract, as detected using the microarray 18 , and they are under the family Veillonellaceae. The genus Rothia is an oral commensal, and Rothia mucilaginosa was recently reported to be increased in current smoker's buccal microbiome 19 , although our analysis in tongue microbiome did not find significant difference in terms of relative abundance. We performed strain sharing pattern analysis to further elucidate the meaning of these differences, and two Veillonella species have relatively high strain sharing within groups compared to between groups.…”
Section: Species_idcontrasting
confidence: 86%
“…Megasphaera micronuciformis were reported to be found more commonly in cigarette smoker's upper gastrointestinal tract, as detected using the microarray 18 , and they are under the family Veillonellaceae. The genus Rothia is an oral commensal, and Rothia mucilaginosa was recently reported to be increased in current smoker's buccal microbiome 19 , although our analysis in tongue microbiome did not find significant difference in terms of relative abundance. We performed strain sharing pattern analysis to further elucidate the meaning of these differences, and two Veillonella species have relatively high strain sharing within groups compared to between groups.…”
Section: Species_idcontrasting
confidence: 86%
“…Smoking is a wellrecognized risk factor for HS (Akdogan et al, 2018;Revuz et al, 2008), but the link between smoking and HS is poorly understood. Cigarette smoking has been shown to alter oral and gut microbiomes (Karabudak et al, 2019;Savin et al, 2018;Wu et al, 2016). Our study, as well as previous reports, did not identify smoking as an independent factor associated with skin dysbiosis in HS (Ring et al, 2017;Schneider et al, 2020).…”
Section: Hs Samples Controlssupporting
confidence: 54%
“…Neither studies found the relative abundance of Rothia to be associated with smoking, but the metagenomic study revealed R. mucilaginosa found in the current smokes to have significantly less gene variations (or strains) compared to the never smokers. However, another study on the buccal microbiome found this species to be enriched by smoking [31].…”
Section: Discussionmentioning
confidence: 96%